O uso do planetário como recurso educacional no ensino de ciências - Silva, Guilherme da Rocha (2019)
Within a scenario where the main indicators that evaluate the level of education of Brazilian public schools reveal a worrying result, mainly in the fields of Exact Sciences, the following work describes an educational activity in a public school, with a methodology approximated to an intervention-research, having been used as an intervention tool a mobile Planetarium, as a non-formal space of education, approaching in this, themes of Astronomy, Mathematics and Physics of high school, with the objective of promoting the immersion and insertion of the student in the field of sciences and a better understanding by them of the concepts of Exact Sciences. The target public was composed by students of the technical courses in Informatics and Buildings of the modality of Professional Education Integrated to High School, who went through a research to survey the knowledge, interest and expectations in the field of Sciences and the discoveries they would experience during the activities with the Planetarium. Thus, a fulldome video was created as Educational Products, to be exhibited in the planetarium with the students, approaching the star formation and the main stars of the Solar System and the Educational Guide: The Solar System, to present to the students the main stars of the System bringing information and illustrations. In addition to seeking a better use of science knowledge by students, the activity aims to promote the dissemination of the planetary as extraordinary educational resources and accessible to teachers and students of schools in the region.